Quality of Life on Chronic Renal Patients Who Running Hemodialysis: A Descriptive Study - Imelda Rahmayunia Kartika; Lisavina Juwita (INDONESIAN NURSING JOURNAL OF EDUCATION AND CLINIC (INJEC), 2018)
Introduction: Patients with Chronic Renal Failure (CRF) cannot survive if they do not do hemodialysis. Therefore, it is necessary to explore the experience, the hope of patients with CRF who undergo hemodialysis in order to continue hemodialysis routinely and can improve the quality of their lives even though their lives depend on hemodialysis. The purpose of this study was to determine the quality of life of patients with CRF in undergoing hemodialysis as an effort to improve the quality of life. Methods: This study was a quantitave study using analytic descriptive approach. There were 66 patients as sample. Data were analyzed using descriptive statistic using World Health Organization Quality of Life Instruments (WHOQoL-Bref) as a quality of life questionnare. Results: This study shows the highest quality of life of research respondents undergoing hemodialysis in the high category (68.2%). This means the quality of life of patients undergoing hemodialysis is good enough. Conclusions: A good quality of life means that the respondent feels satisfied and most of his daily needs can be met, which includes physical, psychological, patient social relations, and the patient's environment. Quality of life is influenced by the physical condition of the individual psychologically, the level of independence, and the relationship of the individual with the environment. Nurses are expected to be able to motivate patients undergoing hemodialysis in improving their quality of life.